2008
DOI: 10.1097/aog.0b013e31819078bd
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Thyroid Hypofunction and Pregnancy Outcome

Abstract: OBJECTIVE-To estimate whether maternal thyroid hypofunction is associated with complications.METHODS-A total of 10,990 patients had first-and second-trimester serum assayed for thyroid-stimulating hormone (TSH), free thyroxine (freeT4), and antithyroglobulin and antithyroid peroxidase antibodies. Thyroid hypofunction was defined as 1) subclinical hypothyroidism: TSH levels above the 97.5th percentile and free T4 between the 2.5th and 97.5th percentiles or 2) hypothyroxinemia: TSH between the 2.5th and 97.5th p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 17 publications
0
28
1
1
Order By: Relevance
“…Figure 1 presents the 16 studies, all of which have been published in the past 20 years. 27 30 34 36 39 50-60 In these mostly prospective observational studies, the cut off used to define subclinical hypothyroidism and the point in gestation at which thyrotropin was assessed varied. Some evaluated fewer than 100 women with subclinical hypothyroidism and are therefore underpowered to detect the pregnancy and neonatal complications studied, which occur in a small proportion of pregnant women.…”
Section: Prevalence Of Subclinical Hypothyroidismmentioning
confidence: 99%
“…Figure 1 presents the 16 studies, all of which have been published in the past 20 years. 27 30 34 36 39 50-60 In these mostly prospective observational studies, the cut off used to define subclinical hypothyroidism and the point in gestation at which thyrotropin was assessed varied. Some evaluated fewer than 100 women with subclinical hypothyroidism and are therefore underpowered to detect the pregnancy and neonatal complications studied, which occur in a small proportion of pregnant women.…”
Section: Prevalence Of Subclinical Hypothyroidismmentioning
confidence: 99%
“…While a number of investigators have reported an increased risk, 54,63-66 larger observational studies comparing preterm delivery rates (<37 weeks) in antibody-positive versus antibody-negative women including Männistö et al (5.9 vs 4.3%), 4,42 Haddow et al 67 (7.5 vs 6.4%) and Abbassi-Ghanavati et al 68 (6.6 vs 5.7%) failed to support these findings. While a number of investigators have reported an increased risk, 54,63-66 larger observational studies comparing preterm delivery rates (<37 weeks) in antibody-positive versus antibody-negative women including Männistö et al (5.9 vs 4.3%), 4,42 Haddow et al 67 (7.5 vs 6.4%) and Abbassi-Ghanavati et al 68 (6.6 vs 5.7%) failed to support these findings.…”
Section: Thyroid Antibodiesmentioning
confidence: 97%
“…The major risk of maternal isolated hypothyroxinemia is the potential for impaired neurodevelopment in offspring. 3,4 The ES supports partial replacement therapy of isolated hypothyroxinemia at the discretion of the caregiver. In 1 study, only 14% of women who initially had low FT4 during early pregnancy remained hypothyroxinemic during pregnancy.…”
Section: Isolated Hypothyroxinemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous studies suggest that subclinical hypothyroidism itself is unlikely to predispose to pre-eclampsia. 4 Many investigators have reported that the plasma concentration of sFlt-1, which binds the angiogenic factors vascular endothelial growth factor and placental growth factor, is raised in pre-eclampsia, and that it rises about five weeks before the clinical diagnosis. 5 In women who developed pre-eclampsia and in controls, the change in thyroid stimulating hormone concentrations from early pregnancy to pre-delivery positively correlated with serum sFlt-1 measured in late pregnancy, with higher concentrations of sFlt-1 being associated with the greatest rise in thyroid stimulating hormone.…”
mentioning
confidence: 99%